A comparison between wishes and status: Gray is not the preference for residents while the city shows neutral colors. Issue 5 (10th April 2017) - Gou, Aiping; Wang, Jiangbo
Abstract: Urban color has become one of the hot topics in China since 2000. To provide suggestions for making the urban color plan for Changzhou of about 253 square kilometers in 2011, the research group evaluated the visual quality of the present architectural color in real urban space and investigated the residential attitude for the present and the future ones. Open‐ended questionnaire of 1065 was taken effectively face to face accompanied with NCS Cascade 980 to understand the residents' attitude about the present architectural color in Changzhou city, and the expectations for the future. At the same time, an overall survey and evaluation on the present architectural color was conducted from the aspects of materials, functions, environmental and color relationship as well as the color code itself. Data reveal the residents' attitude to color preferences is more tolerant in hue with no special color bias, and inclined to those with obvious chroma and clear color predisposition, not very vivid, nor very dark. While the site survey shows the present color focuses mostly in high or middle‐high brightness, neutral ones. In site evaluation and analysis, architecture obtained good scores are those have obviously color predisposition. Colors that are inclined to good scores still have obvious color tendency but is lighter than that of good ones and mostly concentrate in the middle high and high brightness. Although still shows warm colors the most, the color tendency was not so obvious and the proportion of grayish ones increased. As to colors inclined to bad, very large proportion of grayish color existed. Actually, the most insurance color people usually thought, if has no good façade form supporting, is difficult to obtain a pleasant visual effect. Also, if the material is not in agreement with the color, the visual effect will be even worse.